Shade tree species diversity and coffee productivity in Sumberjaya, West Lampung, Indonesia - RUSDI EVIZAL; SUGIATNO SUGIATNO; FEMBRIARTI ERRY PRASMAWATI; INDAH NURMAYASARI (Biodiversitas Journal of Biological Diversity, 2016)
Evizal R, Sugiatno, Prasmatiwi FE, Nurmayasari I. 2016. Shade tree species diversity and coffee productivity in Sumberjaya, West Lampung, Indonesia. Biodiversitas 17: 234-240. Shade tree is an important variable that determines the productivity and sustainability of coffee plantation. In West Lampung, Indonesia coffee is grown on private land and on state land of Community Forest Program (CFP) using various types of shade trees. The research explored the diversity of shade trees and its influence on the productivity of coffee farms. The study area was one purposively sampled coffee farmer group in Sumberjaya District, West Lampung. We purposively chose one coffee farmer group. The group members’ farms located in private land and in CFP land were sampled randomly, each consisted of 18 farms. From each farm, we observed a plot of 50 m x 50 mand interviewed the farmer who managed the farm. Data collected were on the species and the number of trees, farm age, coffee tree densities, and productivity of coffee in the last 3 years. Data analyses of important value, tree species diversity, correlation, and regression were performed. Shade trees found in coffee farms of Sumberjaya were 36 species, 10 species (28%) of them were legume trees. Technical shade trees that have high importance value were Gliricidia sepium and Erythrina subumbrans. Multi Purpose Trees Species (MPTS) widely planted were Durio zibethinus and Parkia speciosa. The wood trees with a high importance value in the CFP coffee farms were Shorea javanica and Michelia champaca while in private coffee farms were Maesopsis eminii and Litsea sp. Based on Shannon’s index (H’) and Simpson’s dominance index (λ), a high diversity of shade tree species was found in CFP coffee farms at age ≥20 years. Shade trees with high dominance index had a positive effect on productivity of coffee and the percentage of MPTS had a negative effect. Whereas, the types of land tenure (private or CFP) and the abundance of shade trees did not affect the productivity of coffee.